Dashboard Analitik Human Capital Development Plan Jabatan Fungsional Manajemen ASN - Elin Cahyaningsih; Inarotul Amani Rizki Ananda; Putri Jihan Ramadhani; Budi Saputro; Rosanti Hidayati (JSAI (Journal Scientific and Applied Informatics), 2025)
The human capital development plan analytics dashboard is a business intelligence tool designed to assist in policy-making and decision-making in the development of competencies and careers of functional officials in ASN management, aiming to improve the quality of ASN management services. The value proposition canvas approach is used to identify problems and analyze user needs to enhance the success of user-based technology implementation. Business intelligence visualization is implemented using the Laravel and Node.js framework with JavaScript programming. Research results show that there are 4 thematic HCDP analytics dashboards, namely HCDP statistics, competency values, competency achievements, and recommendations for the development of functional management ASN position competencies. Future research challenges include improving the availability, accuracy, and integration of technical competency mapping data. However, this dashboard provides a strategic basis for formulating business intelligence recommendation models that will support the sustainable development of JFMASN competencies.